Efek Moderasi Masa Perikatan Audit Pada Hubungan Fee Audit dan Kualitas Audit: Uji Peran Perilaku Oportunistik - Rohma, Frida Fanani; Shofiyah, Indah (Jurnal Inovasi Akuntansi (JIA), 2024)
Based on the agency perspective, the individual is a rational economic man who seeks to optimize his personal interests. Optimization of personal interests along with opportunistic behavior has the potential to reduce audit quality. The aim of this study is to investigate the interaction effect of audit tenure on the audit fees and audit quality relationship. This study uses a quantitative method involving financial companies listed on the Indonesia Stock Exchange as a research sample. The literature is still limited in considering the positive impact of fees and audit tenure on audit quality. However, based on an agency perspective, this study shows that the existence of individual opportunistic behavior is the fundamental reason that aspects of the fee and audit engagement period have the potential to reduce audit quality. The findings of this study also indicate that the audit tenure moderates the effect of audit fees on audit quality. This research contributes to the audit quality literature that audit fees and engagement tenure can be two sword because apart from being able to improve audit quality, in the long term it has the potential to reduce audit quality.